Ethiopia - The Employment Creation Effects of the Addis Ababa Integrated Housing Program - World Bank (World Bank, 2012)
Ethiopia's second poverty reduction strategy, the Plan for Accelerated and Sustained Development to End Poverty (PASDEP) outlines a strategy of complementing a continued strong focus on increasing agricultural productivity with an increased emphasis on urban development. In this context it highlights the importance of facilitating accelerated employment generation to address the issue of high levels of urban unemployment. This report is organized as follows: chapter two provides more detailed background information on the program's operation and goals. Chapter three focuses on the methodology for this study, by articulating the key hypotheses tested in this analysis and identifying its limitations. The chapter also describes the main source of information for this study, a purposively collected survey of firms and workers in the construction sector. Chapter four addresses the central issue of this report by providing a snapshot of the beneficiaries of the program, focusing both on firms and workers and reviewing the effects of the program in terms of employment creation, both in static and in dynamic terms. Chapter five provides evidence on the effectiveness of the support offered by the program, and provides some evidence on the general equilibrium effects of the program. Finally, chapter six provides an assessment of the distributional effects of the program through its employment creation effects. Chapter seven reviews the main conclusions emerging from the study and draws the policy implications for the program, particularly in light o f its ongoing scaling up.